Energy Saver System for Residentiary Application - Azahari, Muhammad Azly Haris; Jenal, Mahyuzie (Evolution in Electrical and Electronic Engineering, 2024)
When compared to energy use in other construction sectors, house buildings have one of the highest levels of energy consumption. The overall yearly energy consumption of houses is between 1,800 and 4,300 kWh per year depending on the size of the building, usage of technology and electrical appliances. The heating and cooling systems, lighting systems, ventilation systems, and house equipment consume the majority of energy in house buildings. The goal of this research is to investigate strategies to save electrical energy in the house by examining the impact of power factor improvement on the electrical appliances by installing capacitor to the electricity bill. Plenty of electrical companies are trying to improve the power utility by studying the usage of power which can be more efficient for the consumers. This technical research work is to design and stimulate the energy saver system that can be apply to a single phase 240 V resident. This work use NI Multisim Analog Device after the design and calculation process.